Carbon Inverse Opal Rods for Nonenzymatic Cholesterol Detection. Issue 43 (28th September 2015) - Zhong, Qifeng; Xie, Zhuoying; Ding, Haibo; Zhu, Cun; Yang, Zixue; Gu, Zhongze
Abstract : Carbon inverse opal rods made from silica photonic crystal rods are used for nonenzymatic cholesterol sensing. The characteristic reflection peak originating from the physical periodic structure works as sensing signals for quantitatively estimating cholesterol concentrations. Carbon inverse opal rods work both in cholesterol standard solutions and human serum. They are suitable for practical use in clinical diagnose.